Reduced densities of parvalbumin- and somatostatin-expressing interneurons in experimental cortical dysplasia and heterotopia in early postnatal development - AKAKIN, DİLEK (ELSEVIER, 2013)
Cortical dysplasia (CD) is strongly associated with intractable epilepsy, probably due to hyperexcitability of neuronal networks. However, the underlying mechanisms are not completely understood. GABAergic interneurons provide major inhibitory function in the CNS and have different subtypes, but it is not clear how each subtype is affected in CD during early post-natal development. We have examined the developmental alterations of the densities of two major subtypes of interneurons, parvalbumin (PV)- and somatostatin (SS)-expressing interneurons in an animal model of CD, in utero irradiation, using immunocytochemistry. We found that the density of PV- and SS-positive interneurons increases significantly in CD and controls during the first three weeks of postnatal life. However, compared to controls, the densities of both subtypes are significantly decreased in CD and heterotopia at all age groups although the time of onset for both PV and SS expression remained unchanged. Our results indicate that the densities of both PV- and SS-positive interneurons are significantly decreased in CD and heterotopia, which may be one important mechanism leading to hyperexcitability of CD. Published by Elsevier B.V.
Keywords: Epilepsy; Cortical dysplasia; Parvalbumin; Somatostatin; Heterotopia; CEREBRAL-CORTEX; ANIMAL-MODEL; IMMUNOREACTIVE NEURONS; SYNAPTIC INHIBITION; RAT MODEL; CALBINDIN; EPILEPSY; EPILEPTOGENICITY; MIGRATION; NEOCORTEX